Sob o estigma do fundamentalismo: algumas reflexões sobre um conceito controverso - Rocha Callapa, Daniel (Horizonte, 2020)
This article seeks to discuss the current inflated use of the concept of fundamentalism (in the media and in academic reflection) and to present some reflections about the limits and controversies surrounding the notion of fundamentalism. From the perspective of the History of Concepts, especially the reflections of Reinhart Koselleck, the text seeks to reconstruct the history of the concept of fundamentalism in America, presenting some essential moments to understand the transformations in the use of the concept throughout the 20th century. The importance of differenciating between “historical fundamentalismo” (Protestant ans American) and its expansion towards “global fundamentalism” - a perspective that gained streght in academia since the 1980s - is emphasized. From this reflections, this article seeks to presente a current debate between defenders of the use of fundamentalism in a comparative perspective and those who consider that the use os an expanded concept of fundamentalism has become more a complicator than a relevant analytical tool in contemporary studies of religion.